Spatio-temporal distribution of dissolved sulfide in China marginal seas - 吴晓丹 吴斌 宋金明 李学刚 (Chinese journal of oceanology and limnology, 2014)
With sulfide increasingly recognized as an important parameter to assess the oxidation-reduction level in aqueous enviromnent, research on its geochemical behavior is becoming important. Water samples collected in Bohai Sea （1-19 August, 2010）, Yellow Sea （20-30 November, 2010） and East China Sea （3-17 June, 2010 and 1-10 November, 2010） were used to determine the occurrence and distribution of dissolved sulfide by methylene blue spectrophotometric method. Results show that： （1） horizontally, concentration of dissolved sulfide significantly varied from the coastal region to the open sea and profoundly influenced by physical processes. High values occurred in the river-sea boundary zone ＂marginal filter＂ due to rich riverine input, frequent upwelling and active exchange in shelf edge. Terrestrial input from adjacent rivers and the current cycling contributed to the high sulfide appeared in western Bohai Sea, eastern Shandong Peninsula, and northeast of Changjiang （Yangtze） River estuary. Especially, relative higher sulfide values occurred in Yellow Sea, which is consistent with the variation of salinity largely due to the hydrodynamic feature; （2） vertically, measurement of dissolved sulfide in bottom water was higher and more variable than that in surface water caused by the wind-induced resuspension and dissimilatory sulfate reduction. Moreover, nutrient-type profile clearly identified that oxidation plays a major role in the biogeochemistry cycle of sulfide in water; （3） seasonally, investigation for East China Sea in June and November reflected seasonal variation of Changjiang River Diluted Water, Kuroshio Current, and Taiwan Warm Current. Concentration in June was much higher than that sampled in November at most stations. Mean concentration of dissolved sulfide varied seasonally from 2.26 μg/L （June） to 1.16 μg/L （November） in surface and 3.00 μg/L （June） to 1.56 μg/L （November） in bottom. Progress in the field is slow and more effort is needed to ensure the accuracy and reliability of determination and estimate the natural or anthropogenic contribution of dissolved sulfide in ecosystems.